Thermal illusions for thermal displays: a review - Karmakar, Subhankar; Kesh, Anindita; Muniyandi, Manivannan (Frontiers in Human Neuroscience, 2023)
Thermal illusions, a subset of haptic illusions, have historically faced technical challenges and limited exploration. They have been underutilized in prior studies related to thermal displays. This review paper primarily aims to comprehensively categorize thermal illusions, offering insights for diverse applications in thermal display design. Recent advancements in the field have spurred a fresh perspective on thermal and pain perception, specifically through the lens of thermal illusions.